Cover Feature: Sol−Gel Processing of Water‐Soluble Carbon Nitride Enables High‐Performance Photoanodes (ChemSusChem 10/2021). Issue 10 (28th April 2021) - Adler, Christiane; Krivtsov, Igor; Mitoraj, Dariusz; dos Santos‐Gómez, Lucía; García‐Granda, Santiago; Neumann, Christof; Kund, Julian; Kranz, Christine; Mizaikoff, Boris; Turchanin, Andrey; Beranek, Radim
Abstract : The Cover Feature shows an ionic carbon nitride photoanode capable of bias‐free photoreforming of alcohols to hydrogen. More information can be found in the Full Paper by C. Adler et al .